Validation of the Work Limitations Questionnaire in Brazilian Army military personnel - Juliane Umann; Rodrigo Marques da Silva; Cristilene Akiko Kimura; Vitor Cauê Lopes; Dirce Bellezi Guilhem (Investigación y Educación en Enfermería, 2018)
Objective To validate the Work Limitations Questionnaire (WLQ) to measure presenteeism in Brazilian military personnel.